2014
DOI: 10.1364/ome.4.000739
|View full text |Cite
|
Sign up to set email alerts
|

Effect of substitution of lutetium by gadolinium on emission characteristics of (Lu_xGd_1-x)_2SiO_5: Sm^3+ single crystals

Abstract: Single crystals of (Lu x Gd 1-x ) 2 SiO 5 :Sm (0.5 at%) with x = 0.19 (81% Gd3+) and x = 0.11 (89% Gd 3+ ) belonging respectively to the C2/c and P2 1 /c space groups were grown by the Czochralski method under nitrogen atmosphere. Detailed investigation of their spectroscopic properties were performed with the aim of understanding the effect of structural modification on emission characteristics of incorporated Sm 3+ ions with a special attention directed to a laser potential associated with yellow emission li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
13
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 23 publications
5
13
0
Order By: Relevance
“…On the other hand, the EDS analysis shown that LGSO crystalline fibers produced by LFZ present compositions close to the initial mixtures, in opposite to compositional dissimilarity observed on LGSO materials developed by conventional CZ method [1,9,52]. The expected structural change at x = 0.17 coming from the Lu amount matches with that reported by literature [1,9,52,62].…”
Section: Lutetium and Gadolinium Oxyorthosilicate (Lgso)supporting
confidence: 78%
See 3 more Smart Citations
“…On the other hand, the EDS analysis shown that LGSO crystalline fibers produced by LFZ present compositions close to the initial mixtures, in opposite to compositional dissimilarity observed on LGSO materials developed by conventional CZ method [1,9,52]. The expected structural change at x = 0.17 coming from the Lu amount matches with that reported by literature [1,9,52,62].…”
Section: Lutetium and Gadolinium Oxyorthosilicate (Lgso)supporting
confidence: 78%
“…However, it is important to highlight that these high refractory silicates were grown by the CZ method [1-5, 35-37, 39-41]. For example, Ryba-Romanovski et al [1] developed solid state yellow lasers based on (Lu x Gd 1-x ) 2 SiO 5 :Sm crystals by CZ, while Wu et al [41] have recently grown Cu co-doped Ce:Lu 2 SiO 5 crystals at 1.5 mm h −1 using a iridium crucible under nitrogen atmosphere for application as scintillators. Furthermore, other approaches for oxyorthosilicates production have been employed during the last years using different methods, like pulsed laser deposition [42], sol-gel [43] or solid-state diffusional process [44].…”
Section: Oxyorthosilicatesmentioning
confidence: 99%
See 2 more Smart Citations
“…These drawbacks can be minimized by using "mixed" oxyorthosilicates (Lu 1−x Ln x )[(SiO 4 ) 0.5 O 0.5 ], which contain not only lutetium but also other REEs [4,[9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%